Distribution pattern of psoriasis, anxiety and depression as possible causes of sexual dysfunction in patients with moderate to severe psoriasis - Alejandro Molina-Leyva; Ana Almodovar-Real; Jose Carlos-Ruiz Carrascosa; Ignacio Molina-Leyva; Ramon Naranjo-Sintes; Jose Juan Jimenez-Moleon (Sociedade Brasileira de Dermatologia, 2015)
Abstract BACKGROUND: Psoriasis may significantly impair sexual function. Depression and organic factors appear to play a key role in this relation. However, beyond genital psoriasis, the importance of the disease's distribution patterns has not been considered. OBJECTIVES: To research sexual function in psoriasis patients and investigate the roles of anxiety, depression and psoriasis' distribution patterns in sexual dysfunction. METHODS: A comparative study matched for sex and age was performed. Eighty patients with moderate to severe psoriasis and 80 healthy controls were included. The participants completed the Massachusetts General Hospital-Sexual Functioning Questionnaire, the Hospital Anxiety and Depression Scale, and the Self-Administered Psoriasis Area and Severity Index. RESULTS: Psoriasis was associated with sexual dysfunction, odds ratio=5.5 (CI 95% 2.6-11.3; p<0.001). Certain distribution patterns of psoriasis, involving specific body regions, were associated with an increase in sexual dysfunction in the group presenting the disease, odds ratio 7.9 (CI 95% 2.3-33.4; p<0.001). Multivariate logistic regression analysis identified anxiety and depression, and the involvement of these specific areas, as possible independent risk factors for sexual dysfunction in patients with moderate to severe psoriasis. CONCLUSION: This study identifies body areas potentially related to sexual dysfunction, independently of anxiety and depression, in psoriasis patients. The results suggest that the assessment of sexual dysfunction and the involvement of these body areas should be considered as disease severity criteria when choosing the treatment for psoriasis patients.